Silibinin sensitizes chemo-resistant breast cancer cells to chemotherapy - Ommoleila Molavi; Farzaneh Narimani; Farshid Asiaee; Simin Sharifi; Vahideh Tarhriz; Ali Shayanfar; Mohammadsaied Hejazi; Raymond Lai (Taylor & Francis Group, 2017)
Context: Multiple drug resistance is the major obstacle to conventional chemotherapy. Silibinin, a nontoxic naturally occurring compound, has anticancer activity and can increase the cytotoxic effects of chemotherapy in various cancer models. Objective: To evaluate the effects of silibinin on enhancing the sensitivity of chemo-resistant human breast cell lines to doxorubicin (DOX) and paclitaxel (PAC). Materials and methods: The cells were treated with silibinin (at 50 to 600 μM concentrations) and/or chemo drugs for 24 and 48 h, then cell viability and changes in oncogenic proteins were determined by MTT assay and Western blotting/RT-PCR, respectively. Flow cytometry was used to study apoptosis in the cells receiving different treatments. The antitumorigenic effects of silibinin (at 200 to 400 μM concentration) were evaluated by mammosphere assay. Results: Silibinin exerted significant growth inhibitory effects with IC50 ranging from 200 to 570 μM in different cell lines. Treatment of DOX-resistant MDA-MB-435 cells with silibinin at 200 μM reduced DOX IC50 from 71 to 10 μg/mL and significantly suppressed the key oncogenic pathways including STAT3, AKT, and ERK in these cells. Interestingly treatment of DOX-resistant MDA-MB-435 cells with silibinin at 400 μM concentration for 48 h induced a 50% decrease in the numbers of colonies as compared with DMSO-treated cells. Treatment of PAC-resistant MCF-7 cells with silibinin at 400 μM concentration generated synergistic effects when it was used in combination with PAC at 250 nM concentration (CI = 0.81). Conclusion: Silibinin sensitizes chemo-resistant cells to chemotherapeutic agents and can be useful in treating breast cancers.